The potential of perylene bisimide derivatives for the solubilization of carbon nanotubes and graphene - Backes, Claudia; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2011)
Carbon nanotubes and graphene are outstanding materials of the 21 century with a broad spectrum of applications. However, major challenges are faced such as the intrinsically low solubility of both sp carbon allotropes. To overcome this hurdle the potential of noncovalent functionalization is summarized with a special focus on the establishment of the perylene bisimide unit as aromatic anchor to the graphitic surface. Rational surfactant design is unmasked as the key to solubilization of the carbon allotropes, while at the same time tailoring their surface properties, or even electronic properties in a fully reversible fashion. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.